KETERLEKATAN SOSIAL ANTARA AKTOR YANG TERLIBAT DALAM DISTRIBUSI KELAPA DI SUNGAI GUNTUNG KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR - Musliyadi "; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Unitary Republic of Indonesia is a country that agrarian, most of the population livesfrom agriculture. many inhabitants choose the type of work in the agricultural sector, among,rubber, oil palm, coconut, rice act. Traced the development of agriculture in Indonesia haveups and downs. This research, used descriptive qualitative method, in data obtained bothfrom interviews, from agencies, observation or other sources are presented in tabular formaccordance with the characteristics of each data. Than data are presented in a simplequalitative descriptive and described or illustrated in accordance with the reality of theembedded between actors involved in the distribution of coconut in Guntung’s riverKateman subdistrict district Indragiri Hilir. By Granovetter (1985), is an economic act besituated socially and attached (embedded) in the personal social networks between theactors. Results of research conducted first oil distribution lines of the palm crop land locatedin the coconut grove harvest period for 3 - 4 months. After harvesting coconuts havecompleted through the process of stripping the oil palm growers will bring using pompongcan reach 5000-8000 cargos of coconut. This Pompong brought the palm to the process ofselling to ship owners or staff purchase in PT. Pulau Sambu depends on the price beenassigned. Than, after sold of coconut, coconut farmer receives form of a memorandum(receipts) is not money received from the sale of coconut farmers. After that coconut farmersbring memorandum (receipts) avidence purchase to owner in order for coconut farmers canreceive the money from the sale. Than, owner bring receipts form a memorandum (receipts)was given to the owner of the ship or purchasing staff of PT. Pulau Sumbu where coconutfarmers sell it than owner may receive compensation from the memorandum evidence(receipts) who submitted.Key words : Embedded, Actor, Coconut Distribution